2013
DOI: 10.3389/fonc.2013.00323
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 Radioembolization in Patients with Hepatocellular Carcinoma Who have Previously Received Sorafenib

Abstract: Purpose: Yttrium-90 radioembolization (RE) is a locoregional therapy option for hepatocellular carcinoma (HCC). Sorafenib is a multikinase inhibitor used in HCC that can potentially affect the efficacy of RE by altering tumor vascularity or suppressing post-irradiation angiogenesis. The safety and efficacy of sorafenib followed by RE has not been previously reported.Materials and Methods: Patients with HCC who received RE after sorafenib were included in this retrospective review. Overall survival, toxicity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Our results, derived from a cohort of patients whose disease, at baseline, was more severe than that experienced by patients in the sharp trial, still showed comparable survival results. However, those survival data contrast with data from a study by Rana et al 53 , who retrospectively reviewed 10 patients receiving sorafenib followed by radioembolization. In their study, which included 7 patients classified as Child-Pugh A and 3 classified as Child-Pugh B, the side effects with combined therapy were similar to those reported here-namely, anorexia, fatigue, gastrointestinal symptoms, and also the more severe side effects related to ascites and liver enzymes-and yet their reported overall survival duration was barely greater than 7 months, which is worse than the survival durations associated with both therapies alone.…”
Section: Discussionmentioning
confidence: 77%
“…Our results, derived from a cohort of patients whose disease, at baseline, was more severe than that experienced by patients in the sharp trial, still showed comparable survival results. However, those survival data contrast with data from a study by Rana et al 53 , who retrospectively reviewed 10 patients receiving sorafenib followed by radioembolization. In their study, which included 7 patients classified as Child-Pugh A and 3 classified as Child-Pugh B, the side effects with combined therapy were similar to those reported here-namely, anorexia, fatigue, gastrointestinal symptoms, and also the more severe side effects related to ascites and liver enzymes-and yet their reported overall survival duration was barely greater than 7 months, which is worse than the survival durations associated with both therapies alone.…”
Section: Discussionmentioning
confidence: 77%
“…These two observations raise the question whether the pretransplant intolerance to sorafenib and the post-transplant biliary complications and rejection signify a safety signal regarding sorafenib therapy as a neo-adjuvant in patients receiving RE. Doubts regarding the usefulness of adding sorafenib to RE in patients not referred for LT, have already risen following a retrospective analysis of a small study in which 10 HCC patients with BCLC stage C were treated with sorafenib prior to RE [17]. In this study, overall survival of patients with advanced HCC receiving a combination of RE and sorafenib was lower compared to historical data in patients treated with RE or sorafenib alone.…”
mentioning
confidence: 83%
“… 61 This is the fundamental aim of the emerging studies on the combination of TARE and sorafenib. 115 117 …”
Section: Tare Proceduresmentioning
confidence: 99%